Critical Angiographic and Sonographic Analysis of Intra Aneurysmal and Downstream Hemodynamic Changes After Flow Diversion - Raychev, Radoslav; Sirakov, Stanimir; Sirakov, Alexander; Saber, Hamidreza; Vinuela, Fernando; Jahan, Reza; Nour, May; Szeder, Viktor; Colby, Geoffrey; Duckwiler, Gary; Tateshima, Satoshi (Frontiers in Neurology, 2022)
Introduction: Successful treatment of intracranial aneurysms after flow diversion (FD) is dependent on the flow modulating effect of the device. We aimed to investigate the intra-aneurysmal and parent vessel hemodynamic changes, as well as the incidence of silent emboli following treatment with various FD devices. Methods: We evaluated the appearance of the eclipse sign in 9 distinct phases of cerebral angiography before and immediately after FD placement in correlation with aneurysm occlusion. Angiographic and clinical data of consecutive procedures was analyzed retrospectively. Patients who had successful FD procedure without adjunctive coiling, visible eclipse sign on post embolization angiography, and reliable follow up angiographic data were included in the analysis. Detailed analysis of hemodynamic data from transcranial doppler after FD was also performed in selected patients, including monitoring for silent emboli. Results: Among all patients (N=65) who met inclusion criteria, complete aneurysm occlusion at 12 months was achieved in 89% (58/65). Eclipse sign prior to FD was observed in 42% (27/65) with unchanged appearance in 4.6% (3/65) of the treated patients. None of these 3 patients achieved complete aneurysm occlusion. Among all analyzed variables including aneurysm size, device type used, age, appearance of the Eclipse sign pre and post FD, the most reliable predictor of permanent aneurysm occlusion at 12 months was earlier, prolonged, and sustained eclipse sign visibility in more than 3 angiographic phases in comparison to baseline (p < 0.001). Elevation in flow velocities within the ipsilateral vascular territory was noted in 70% (9/13) , and bilaterally in 54% (7/13) of the treated patients. None of the patients had silent emboli Conclusions: Intra-aneurysmal and parent vessel hemodynamic changes after flow diversion can be reliably assessed by cerebral angiography and transcranial doppler with important implications for prediction of successful treatment.